2014
DOI: 10.1016/j.ahj.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Association between prehospital electrocardiogram use and patient home distance from the percutaneous coronary intervention center on total reperfusion time in ST-segment–elevation myocardial infarction patients: A retrospective analysis from the National Cardiovascular Data Registry

Abstract: Background Current guidelines recommend ≤90 minutes from first medical contact (FMC) to percutaneous coronary intervention (FMC2B) for ST segment elevation myocardial infarction (STEMI) patients. We evaluated the relationship between patient home distance from a percutaneous coronary intervention (PCI) center, prehospital electrocardiogram (ECG) use, and FMC2B time among patients with STEMI. Methods We performed a retrospective cohort study including all STEMI patients in the ACTION®-GWTG™ registry from 7/1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…32 Mumma et al noted that prehospital ECG is associated with a 10-min reduction in the first medical contact-to-device interval. 33 In that study, the median transfer distance was 17 km (IQR, 9.3-34.6 km), whereas in the present study it was 7.0 km (IQR, 4.5-9.1 km); moreover, on univariate analysis, transfer distance was not an independent predictor of door-device interval <90 min. This suggests that the association between prehospital ECG and first medical contact-to-device interval may differ between rural areas and urban areas such as Suita City.…”
Section: Mts Prehospital Ecg Transmission Decreases Time To Reperfusioncontrasting
confidence: 42%
“…32 Mumma et al noted that prehospital ECG is associated with a 10-min reduction in the first medical contact-to-device interval. 33 In that study, the median transfer distance was 17 km (IQR, 9.3-34.6 km), whereas in the present study it was 7.0 km (IQR, 4.5-9.1 km); moreover, on univariate analysis, transfer distance was not an independent predictor of door-device interval <90 min. This suggests that the association between prehospital ECG and first medical contact-to-device interval may differ between rural areas and urban areas such as Suita City.…”
Section: Mts Prehospital Ecg Transmission Decreases Time To Reperfusioncontrasting
confidence: 42%
“…Similar sex differences in EMS protocol adherence have been demonstrated in chest pain and STEMI, with women less likely to receive prehospital electrocardiograms and aspirin. 11,12 Importantly, our data suggest that sex differences in prehospital medication administration are not driven primarily by differences in IV/IO access.…”
Section: Discussionmentioning
confidence: 64%
“…10,11 Similarly, important sex differences may occur in prehospital interventions for OHCA. In this study, we use the Resuscitation Outcomes Consortium (ROC) Prehospital Resuscitation using an IMpedance valve and Early versus Delayed (PRIMED) database to determine whether sex differences exist in prehospital treatment intervals, procedures, and medications among adults with OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…Although we demonstrate significant increases over the study period in proportions with a prehospital ECG for patients with and without OHCA taken directly to a PCI hospital, substantial differences remained in relation to not only the transfer‐in counterparts but also between patients with and without OHCA who were transported directly to a PCI hospital. Despite significantly more patients having prehospital ECGs both over time and in comparison to previous ACTION REGISTRY‐GWTG studies, these previous ACTION REGISTRY‐GWTG studies demonstrated that prehospital ECGs were associated with greater use of reperfusion therapy, faster reperfusion times, and a trend for lower mortality 1, 15, 16. Although use of prehospital ECGs increased for patients taken directly to a PCI‐capable facility, the use of prehospital ECGs decreased over time for transfer‐in patients, and patients with OHCA were significantly less likely to have a prehospital ECG obtained over time relative to their counterparts without OHCA.…”
Section: Discussionmentioning
confidence: 89%